Reassessment of Relevance and Predictive Value of Parameters Indicating Early Graft Dysfunction in Liver Transplantation: AST Is a Weak, but Bilirubin and INR Strong Predictors of Mortality - Fodor, Margot; Woerdehoff, Adriana; Peter, Wolfgang; Esser, Hannah; Oberhuber, Rupert; Margreiter, Christian; Maglione, Manuel; Cardini, Benno; Resch, Thomas; Weissenbacher, Annemarie; Sucher, Robert; Zoller, Heinz; et al. (Frontiers in Surgery, 2021)
Introduction: Early graft dysfunction (EAD) complicates liver transplantation (LT). The aim of this analysis was to discriminate between the weight of each variable as for its predictive value towards patient and graft survival. Methods: We reviewed all LT performed at the Medical University of Innsbruck between 2007 and 2018. EAD was recorded when one of the following criteria was present: (i) aspartate aminotransferase (AST) levels >2000 IU/L within the first seven days, (ii) bilirubin levels ≥10mg/dL or (iii) international normalized ratio (INR) ≥1.6 on postoperative day 7. Results: Of 616 LT, 30.7% developed EAD. Patient survival did not differ significantly (P=.092; log rank-test=2.87), graft survival was significantly higher in non-EAD patients (P=.008; log rank-test=7.13). Bilirubin and INR on postoperative day 7 were identified as strong mortality predictors (Bilirubin HR=1.71 [1.34, 2.16]; INR HR=2.69 [0.51, 14.31]), in contrast to AST (HR=0.91 [0.75, 1.10]). Similar results were achieved for graft loss estimation. A comparison with the Model for Early Allograft Function (MEAF) and the Liver Graft Assessment Following Transplantation (L-GrAFT) score identified a superior discrimination potential but lower specificity. Conclusion: Contrarily to AST, bilirubin and INR have strong predictive capacity for patient and graft survival. This fits well with the understanding, that bile duct injury and deprivation of synthetic function rather than hepatocyte injury are key factors in LT.